The inking woman : 250 years of women cartoon and comic artists in Britain - Streeten, Nicola; Tate, Cath, 1951-; Cartoon Museum (London, England) (Oxford : Myriad editions, 2018)
For many years, the world of cartoons and comics was seen as a male preserve. The reality is that women have been drawing and publishing cartoons for longer than most people realise. In the early 1760s, Mary Darly illustrated, wrote and published the first book on caricature drawing published in England, A Book of Caricaturas. In the nineteenth century, Britain's first comic character, Ally Sloper, was developed by the actress and cartoonist Marie Duval (1847-1890). Cartoons were used by the suffragettes, and, during the Great War, artists such as Flora White and Agnes Richardson produced light-hearted propaganda comic postcards.; From the 1920s, a few women cartoonists began to appear regularly in newspapers. The practice was for artists to sign with their surname, so most readers were unaware of the cartoonist's gender. In 1920, Mary Tourtel created Rupert Bear for the Daily Express, and nearly a hundred years later her character is still going strong. From the 1960s, feminism inspired cartoonists to question the roles assigned to them and address subjects such as patriarchy, equal rights, sexuality and child rearing, previously unseen in cartoons. Over the last thirty years, women have come increasingly to the fore in comics, zines and particularly graphic novels; This wide-ranging curation of women's comics work includes prints, caricatures, joke, editorial and strip cartoons, postcards, comics, zines, graphic novels and digital comics, covering all genres and topics. It addresses inclusion of art by women of underrepresented backgrounds. Based on an exhibition of the same name, held at the Cartoon Museum in 2017, this book demonstrates that women have always had a wicked sense of humour and a perceptive view of the world.
Companion to exhibition held at the Cartoon Museum, London, in 2017.
Includes bibliographical references (page 140) and index.
Keywords: Women cartoonists -- Great Britain -- Exhibitions; Women cartoonists -- Great Britain -- History; Women cartoonists -- Great Britain -- Biography